Signalling pathways in a nutshell: from pathogenesis to therapeutical implications in prostate cancer - Goncharov, Aviv Philip; Dicusari Elissaiou, Constantinos; Ben Aharon Farzalla, Elad; Akhvlediani, Giorgi; Vashakidze, Nino; Kharaishvili, Gvantsa (Annals of medicine, 2025)
From tumorigenesis to the establishment of local or metastatic high-grade tumours, an integral part of the cellular lifespan relies on various signalling pathways. Particular pathways that allow cells to proliferate by creating a network of new blood vessels have been documented, whereas other pathways are primarily involved with a migration to distant body parts, partially through the process of epithelial-mesenchymal transition (EMT). This review will discuss the different signalling pathways, such as TGF-β, Cripto-1, Wnt pathways, Hedgehog, Notch and NF-κB pathways, and how they promote tumour initiation and progression by influencing diverse cellular processes and EMT in general and in benign and malignant prostate tumours. This review will discuss only the critical pathways. Therefore, many other types of signalling pathways which are related to prostate cancer will not be discussed. Possibilities for further investigation will be mentioned, as many underlying mechanisms involved in these pathways have potential as targets in future tumour therapy. This review will also introduce some novel clinical trials relating to the inhibition of signalling pathways and their clinical outcomes.
Keywords: NF-κB; Prostatic Neoplasms; signální transdukce; Signal Transduction; nádory prostaty; proteiny hedgehog; Humans; therapeutic target; Prostate cancer; epitelo-mezenchymální tranzice; TGF; Notch; lidé; castration resistance; Hedgehog; β; Epithelial-Mesenchymal Transition; WNT/β-catenin; Hedgehog Proteins; signalling pathways; Male; transformující růstový faktor beta; Transforming Growth Factor beta; EMT; NF-kappa B; mužské pohlaví